Trends in Tax Avoidance at PT Bentoel Internasional Tbk: An Evaluation Based on Effective Tax Rate (ETR) and Cash Effective Tax Rate (CETR) - Yuyun Kurniawati; Khariidatul Bahiyyah (Jurnal Wacana Ekonomi, 2026)
Tax avoidance is a significant issue in corporate governance, particularly among multinational companies that have the flexibility to exploit cross-jurisdictional regulatory gaps. This study aims to analyze tax avoidance trends at PT Bentoel Internasional Investama during the 2013–2022 period using the indicators Effective Tax Rate (ETR) and Cash Effective Tax Rate (CETR). This research employs a quantitative descriptive method based on secondary data obtained from the company’s financial statements. The findings show variations in ETR and CETR across years, including extreme values such as zero, negative, and above 100%. Low ETR and CETR values in certain years indicate potential tax avoidance practices, which may be influenced by company losses, timing differences in tax expense recognition, or tax management strategies. This study provides insights into the effectiveness of ETR and CETR as indicators for detecting potential tax avoidance practices. The findings indicate that differences between ETR and CETR significantly reflect variations in the intensity of corporate tax planning, suggesting that statutory tax rates cannot serve as the sole indicator of tax compliance. Furthermore, inconsistencies between accounting standards and tax regulations create opportunities for regulatory arbitrage, enabling firms to legally optimize their tax burdens. These results also imply that multi-year analysis is more relevant for evaluating tax behavior and assessing corporate tax aggressiveness.